Manajemen Persediaan dengan Metode ABC, Hierarchical Clustering, dan EOQ Untuk Menentukan Reorder Point - Aditya Bagus Wicaksana; M Amin Syukron; Melinska Ayu Febrianti; Qurtubi Qurtubi (OPSI, 2020)
PT XYZ is a company that produces various types of laundry machine with variety of capacity. It is important for a company to maintain the quality of production. The large number of different components originated from several suppliers scattered in several locations, require proper planning to avoid lack of parts or excessive of parts stored in the warehouse. The method of Activity Based Costing (ABC) and Hierarchical Clustering are employed to determine products and main components that are prioritized, as well as to perform reorder point calculation for product’s main components. The result of research identifies five raw materials that should be prioritized and considered, which are Old Version Rad Radiator, As VCN D 50 mm (Length of 60 cm) Black PlatEser MS 1 mm, Motor 1 HP 3 Phase 4 pole B3 Toshiba, and Steam trap S31N Miyawaki 1.6 MPA 220 Degree 15 mm ½”. Reorder point for old radiator could be carried out on the 4th day with safety stock of 2 units. Maximum storage is determined for 6 units with EOQ of 4 units.